Implementation of Regional Tax Payments via Standard Indonesian Quick Response (Qris) at the Regional Revenue Agency of Palopo City - Muh. Yusril (JEKAMI Journal of Accounting, 2023)
QRIS is a payment system that is the QR Code standard for digital payments via electronic applications so that transactions can be more efficient. QRIS was developed by Bank Indonesia together with the payment system industry which can process transactions quickly, easily and safely. The aim of this research is to determine the benefits of implementing regional tax payments through QRIS at the Regional Revenue Agency of Palopo City. The research object of this final assignment is "Implementation of regional tax payments via Quick Response Indonesia Standard (QRIS) at the Regional Revenue Agency of Palopo City" . Type of research carried out using an applied qualitative approach. The data collection technique used is the Interview, Documentation and Observation method. The results of this research show that people are still unfamiliar with the existence of QRIS as a digital channel that can be used to carry out regional tax and regional levy payment transactions, so systematic and massive efforts are needed to socialize and educate about the existence of QRIS.